PENGUATAN RESTORATIVE JUSTICE MELALUI PENDEKATAN ADAT DAN KEARIFAN LOKAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PIDANA ANAK - Wencislaus Sirjon Nansi; Wahyu Jontah (Jurnal Ilmu Hukum, 2018)
The child is the future and the next generation of the ideals of the nation, therefore the best interests of the child must be the responsibility of all parties. The Including the interests of children who are faced with the law. In the Criminal Justice System Law No. 11 of 2012 recognizes Justice's restorative approach in the settlement of child criminal cases. Restorative justice approach is intended to prevent children from the impression of criminal and psychological trauma due to the judicial process and also besides that restorative justice approach is an effort to restore the balance between the perpetrator and the victim, as well as the perpetrator with the community to the original state. One of the most important approaches to restorative justice is the traditional approach and local wisdom. Customary law and local wisdom should be an alternative solution in the realization of restorative justice. Therefore this paper intends to examine the legitimacy of customary law in the legal system in Indonesia and the extent to which it exists within the Criminal Justice System law. The method used in this paper is the normative approach. Based on the results of the study it was found that restorative justice through indigenous approaches and local wisdom has not been seriously accommodated in the Criminal Justice System Law. Customary law in the form of fulfillment of customary obligations is only considered as an additional criminal. The additional criminal principle is not independently dependent on the principal penalty. Should the state seriously apply the principle of restorative justice in the settlement of child criminal cases, the customary approach should be regarded as one of the main forms of the crime.